Training on the Utilization of Culturally Responsive Teaching Approach in Implementing Liberating Learning for Students at SD Negeri 8 in Bengkulu City - Purwanto, Andik; Putri, Desy Hanisa; Hamdani, Dedy; Arincia, Meicella Rizky; Koto, Irwan; Gunawan, Bodi; Muhammad, Adamu Abubakar (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service aims to provide training to teachers at SD Negeri 8 Bengkulu City in utilizing the CRT approach to implement learning that liberates students. The training activity was carried out on April 27 2024 at SD Negeri 8 Bengkulu City and was attended by 13 teachers. Training methods are carried out in the form of lectures, discussions and practice. In the first session, participants were provided with an understanding of the concept of CRT and the importance of integrating culture in learning. The second session discussed identifying students' cultural backgrounds and learning strategies that are appropriate to the CRT approach. The final session focused on classroom management from a CRT perspective, evaluation, and collaboration with parents and the community. The training activity was carried out at SDN 8 Bengkulu City, which was attended by 13 teachers. Through this training, it is hoped that teachers can develop the ability to create a learning environment that is culturally responsive, respects diversity, and liberates students in the learning process. Activities are carried out using training patterns. After conducting training, teachers were able to develop teaching modules using the CRT approach. From this training activity it can be concluded that the training has an impact on the ability of teachers to develop teaching modules using the CRT approach.